A Novel Approach to Monitoring of the Diffusion Junction Potential in Speciation Studies by Polarography under very Acidic Conditions. Part II: The Quasi‐Reversible Cu(II)‐Picolinic Acid System. Issue 2 (15th December 2014) - Billing, Caren; Cukrowski, Ignacy
Abstract The use of polarography to accurately determine stability constants of complexes formed under very acidic conditions (below pH 2) is demonstrated. The diffusion junction potentials, which must be accounted for below pH 2, were evaluated by applying protocols developed where Tl(I) is used as an internal reference. The Cu(II)‐picolinic acid (2‐pyridinecarboxylic acid) system studied was chosen since the CuL+ species only exists in solution below pH 2 under the conditions used and literature data exists to confirm the accuracy of procedure. Additionally, the reduction of Cu(II) was quasi‐reversible and procedures to determine the reversible half‐wave potentials were investigated. Average log β values of 7.75±0.09 for CuL+ and 14.8±0.1 for CuL2 were obtained, which compared well to literature data.